Complementary Feeding Recommendations for A Healthy Future Generation - Gizem Yonar; Ayçıl Özturan Şirin (Trends in Pediatrics, 2022)
World Health Organization data remark that 144 million children under the age of 5 are stunted by age. In Turkish society, the high weakness and stunting rates, especially among children aged 6-8 months, are an indication that complementary nutrition practices are not given enough importance in our country. Therefore, this review, it is aimed to emphasize the importance of complementary feeding in terms of the risk of malnutrition among children and to give an example of current complementary feeding practices. It is stated that at the beginning of the 5th month, infants neuromuscular development, digestive system, and renal solute load are suitable for complementary feeding. In addition to breast milk, complementary foods should include cereals, roots and tubers, legumes, nuts and seeds, dairy, meats, eggs, vegetables and fruits rich in vitamin A. Foods with allergy risk, such as eggs and peanuts should be tried for infants between 4 and 6 months. Along with breast milk, it is stated that 6-8-month olds are fed 2 or 3 times a day, and 9-11-months-old fed 3 or 4 times a day and should be paid attention to hunger and satiety signals. Complementary feeding should be started at 2 or 3 teaspoons and be increased considerably and transition should be made from pureed foods lumpy foods, finger foods and then chopped family foods until they are 12 months old. During the first year, vitamin D and iron micronutrient supplementation should be followed. It is recommended for infants to sip water instead of sugary drinks like fruit juices at meals and to introduce gluten to infants between 4 and 12 months. It is warned not to add sugar, salt and honey to the complementary feeding. To reduce the risk of malnutrition among children in Türkiye, complementary feeding should be given due significance.